Coping strategies to exposure to workplace bullying - Malgorzata Gamian-Wilk; Brita Bjorkelo; Kamila Madeja-Bien (University of Lower Silesia, 2017)
The article concerns coping strategies of workers subjected to workplace bullying. Firstly, bullying process development is compared with various models of conflict escalation. Secondly, the review of literature on employees' exposed to bullying at work responses to negative workplace activities is presented. Finally, the results of studies comparing targets' and non-targets' strategies on various stages of bullying development are described. The findings indicate that employees previously exposed to bullying at work at the very early stage of conflict respond in a way that may be interpreted as unconstructive while those who encounter single conflicts at work intensify their endeavors to make a good impression, and try to gain social support from their surrounding interpersonal relationships. Bullying targets seek support and use strategies based on co-operation when the conflict is severe and difficult to solve. The article ends with directions for future studies aiming at identifying strategies for prevention programs.